Skip to content
Home » List of Logical Equivalences and Truth Tables

List of Logical Equivalences and Truth Tables

    In this article, you will know the list of known logical equivalences and their corresponding truth table as a proof of them being a tautology. To understand more in-depth analysis of each of the identities, you can watch my YouTube channel.

    Note that these logical identities are also found in Boolean algebra and each of the logical identity has its dual obtained by inverting the connectives and True or False if any.

    Logical Equivalences with And, Or, Not

    These are logical equivalence that use following connectives – conjunction, disjunction and negation.

    Identity Laws

    \begin{aligned} p \wedge T \equiv p\end{aligned}
    T
    TTT
    FTF
    \begin{aligned}p \vee F \equiv p\end{aligned}
    F
    TFT
    FFF

    Domination Laws

    \begin{aligned}p \vee T \equiv T\end{aligned}
    T
    TTT
    FTT
    \begin{aligned}p \wedge F \equiv F\end{aligned}
    F
    TFF
    FFF

    Idempotent Laws

    \begin{aligned}p \wedge p \equiv p\end{aligned}
    TT
    FF
    \begin{aligned} p \vee p \equiv p\end{aligned}
    TT
    FF

    Double Negation Law

    \begin{aligned}\neg (\neg p) \equiv p\end{aligned}
    TFT
    FTF

    Commutative Laws

    \begin{aligned}p \wedge q \equiv q \wedge p\end{aligned}
    TTTT
    TFFF
    FTFF
    FFFF
    \begin{aligned}p \vee q \equiv q \vee p\end{aligned}
    TTTT
    TFTT
    FTTT
    FFFF

    Associative Laws

    \begin{aligned}p \wedge (q \wedge r) \equiv (p \wedge q) \wedge r\end{aligned}
    TTTTTTT
    TTFFFTF
    TFTFFFF
    TFFFFFF
    FTTTFFF
    FTFFFFF
    FFTFFFF
    FFFFFFF
    \begin{aligned}p \vee (q \vee r) \equiv (p \vee q) \vee r\end{aligned}
    TTTTTTT
    TTFTTTT
    TFTTTTT
    TFFFTTT
    FTTTTTT
    FTFTTTT
    FFTTTFT
    FFFFFFF

    Distributive Laws

    \begin{aligned} p \wedge (q \vee r) \equiv (p \wedge q) \vee (p \wedge r)\end{aligned}
    TTTTTTTT
    TTFTTTFT
    TFTTTFTT
    TFFFFFFF
    FTTTFFFF
    FTFTFFFF
    FFTFFFFF
    FFFFFFFF
    \begin{aligned} p \vee (q \wedge r) \equiv (p \vee q) \wedge (p \vee r)\end{aligned}
    TTTTTTTT
    TTFFTTTT
    TFTFTTTT
    TFFFTTTT
    FTTTTTTT
    FTFFFTFF
    FFTFFFTF
    FFFFFFFF

    Absorption Laws

    \begin{aligned} p \wedge (p \vee q) \equiv p\end{aligned}
    TTTT
    TFTT
    FTTF
    FFFF
    \begin{aligned} p \vee (p \wedge q) \equiv p\end{aligned}
    TTTT
    TFFT
    FTFF
    FFFF

    Negation Laws

    \begin{aligned}p \wedge \neg p \equiv F\end{aligned}
    F
    TFFF
    FTFF
    \begin{aligned}p \vee \neg p \equiv T\end{aligned}
    T
    TFTT
    FTTT

    De Morgan’s Laws

    \begin{aligned}\neg(p \wedge q) \equiv \neg p \vee \neg q\end{aligned}
    TTFFTFF
    TFFTFTT
    FTTFFTT
    FFTTFTT
    \begin{aligned}\neg(p \vee q) \equiv \neg p \wedge \neg q\end{aligned}
    TTFFTFF
    TFFTTFF
    FTTFTFF
    FFTTFTT
    Exit mobile version